2022
DOI: 10.32604/ee.2022.016151
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Decision-Making of Trans-Provincial Electricity Market Subjects with Risks under Renewable Portfolio Standards

Abstract: The randomness and uncertainty of renewable energy generation are expected to significantly change the optimal decision-making of trans-provincial electricity market subjects. Therefore, it is beneficial to optimize the interests of each of these subjects, considering the unpredictable risks of renewable energy under the renewable portfolio standards (RPS) and researching their effects on the optimal decision-making of transprovincial electricity market multi-subjects. First, we develop a trans-provincial trad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…In addition, the coupled interaction between TGCs and the power market has a significant impact on the behavior of power producers [19,20]. For example, Wang et al [21] constructed a decision-optimization model considering subjects' preferences and utility, and the results showed that TGC price is an important factor affecting the profitability of energy manufacturers. (3) Exploration of TGC price mechanisms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, the coupled interaction between TGCs and the power market has a significant impact on the behavior of power producers [19,20]. For example, Wang et al [21] constructed a decision-optimization model considering subjects' preferences and utility, and the results showed that TGC price is an important factor affecting the profitability of energy manufacturers. (3) Exploration of TGC price mechanisms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, these power packages lacked universality because of the assumption that RES purchase costs could be ignored. An optimal decision model for each trading subject was then constructed under the conditions of supply chain noncooperation and cooperation [25].…”
Section: Progress Of China's Renewable Portfolio Standardsmentioning
confidence: 99%
“…Zhang et al [41] has proposed building a renewable energy market trading plan with electricity sales companies as the main body and renewable energy trading volume as an evaluation indicator. Wang et al [25] has also put forward planning and construction suggestions for establishing a multi-level renewable energy trading market on a time scale. Further, Huang et al [35] has formulated two different renewable energy retail schemes according to user needs and analyzed the purchasing and selling decision behavior of electricity companies from the implementation of the quota system and environmental benefits.…”
Section: Design Concept Of the Renewable Portfolio Standards Mechanis...mentioning
confidence: 99%
“…The key determinant of the game decision of each interest group under the RPS policy lies in the cost and benefit mechanism in the process of completing the RPSs [24]. Specifically, it is important for power generation enterprises to determine whether and what they could obtain from renewable energy generation and whether their renewable electricity generation could be fully accessed through the grid.…”
Section: Stakeholders In Rpsmentioning
confidence: 99%